A rare case of tracheal lymphoma presenting with severe tracheal stenosis [«Un raro caso di linfoma della trachea con stenosi severa»] - (:unkn) unknown (Mattioli 1885 S.p.A., 2015)
Primary malignant lymphoma of the trachea is rare and its underlying mechanism remains unknown. Primary tracheal tumors are also very rare causes of airway obstructions. This case report features a 60 year-old woman who presented with the complaint of dyspnea. A mass narrowing the tracheal lumen posteriorly in the subglottic area and mediastinal lymphadenopathy was detected by computed tomography scan and a rijit bronchoscopy was performed. This showed polypoid, variable-sized, irregular nodules causing narrowing of the tracheal lumen over a 3 cm segment in the middle part of the trachea and a mass protruding into the tracheal lumen from the posterior part of the proximal trachea. Multiple biopsy was carried out from the nodules and the airway obstruction was treated with Argon Plasma Coagulation (APC). After removal of the debris, tracheal lumen patency was obtained. The histopathology examination revealed a small lymphocytic primary non-Hodgkin’s lymphoma of the trachea. To our knowledge, this is the first case of small lymphocytic primary tracheal lymphoma in the literature. © Mattioli 1885.
Keywords: Interventional bronchoscopy; Tracheal lymphoma; Tracheal stenosis